IMPLEMENTASI LOGIKA FUZZY MAMDANI PADA PREDIKSI INDEKS PEMBANGUNAN MANUSIA PROVINSI KEP. BANGKA BELITUNG TAHUN 2010-2023 - Halim, Nikken; Sakti, Adam Indra; Lutfiyaturrohmah, Khilma; Pramita, Agnes; Prayanti, Baiq Desy Aniska (MATHunesa: Jurnal Ilmiah Matematika, 2025)
The Human Development Index is a comprehensive picture of the level of human development in a region, as the impact of development activities carried out in that region. There are three basic dimensions as a benchmark for measuring the Human Development Index that covers longevity and healthy living, knowledge, and a decent standard of living. Fuzzy logic is one of the decision support systems that can be implemented for uncertainty issues. The aim of this research is to implement the fuzzy logic of the Mamdani method on the Human Development Index (HDI) prediction and obtain accurate results from such implementation. The research variables used were life expectancy, average school age, school age expectation and per capita expenditure. This research will be done with the help of Matlab software. Based on the implementation of the fuzzy logic of the Mamdani method on the IPM prediction, the MAPE value is obtained with an average of 0.087169912% which means that it has a true value of 99.91283009%. This shows that the Fuzzy Logic of Mammdani's method is well used to predict IPM in the Bangka Belitung Islands Province.